FORMULASI KRIM ANTI JERAWAT DARI NANOPARTIKEL KITOSAN CANGKANG UDANG WINDU (PENAEUSMONODON) - Radhia Riski; Fitriyanti Jumaetri Sami (Jurnal Farmasi UIN Alauddin Makassar, 2015)
Chitosan has the potential to be used as an antimicrobial agent, as it contains the enzyme lysozyme and aminopolisakarida groups which can inhibit the growth of microbes. Physical modification of chitosan in the form of nanoparticles add value to chitosan as an antimicrobial material. In this research, anti-acne cream was formulated by using nanoparticles chitosan with variations emulsifier  that are Novemer®, Span-Tween, and Viscolam®. The cream  then evaluated for physical stability include kriming volume, the thickness (viscosity), drops dispersed, and phase inversion before and after accelerated storage conditions. Then, test of antibacterial activity against Propionibacterium acne was performed. The results showed that the three creams were physically stable during storage. Formula cream with tween span emulsifier (FII) showed the greatest inhibition against Propionibacterium acne with a diameter of 13.46 mm zone of inhibition.